Electricity over glass [fiber optic to transfer electric power]. - Basanskaya, A. (IEEE spectrum)
Photonic Power Systems Inc. has developed a system that uses a laser to inject power in the form of light into a fiber-optic cable and photovoltaic (PV) array to convert the light back into electricity for powering devices. This paper discusses the use of optical fiber instead of copper wire in power delivery. This method of power transfer is highly advantageous in situations where sparks or shorts can be a fatal problem, where electromagnetic interference is more than just an inconvenience. At the heart of the system is an array of PV cells whose efficiency is achieved by converting light at whatever frequencies the sun provides.